Digital design from zero to one - Daniels, Jerry, 1948- (New York : John Wiley and Sons, 1996)
This book is about: Combanational logic; Sequential design; Mastering design; ...
Keywords: Engineering; Data processing; Digital integrated circuits; Digital integrated circuits -- Design and construction -- Data processing